2009
DOI: 10.1007/s00125-009-1436-2
|View full text |Cite
|
Sign up to set email alerts
|

A susceptibility gene for type 2 diabetes confers substantial risk for diabetes complicating cystic fibrosis

Abstract: Aims/hypothesis Insulin-requiring diabetes affects 25-50% of young adults with cystic fibrosis (CF). Although the cause of diabetes in CF is unknown, recent heritability studies in CF twins and siblings indicate that genetic modifiers play a substantial role. We sought to assess whether genes conferring risk for diabetes in the general population may play a risk modifying role in CF. Methods We tested whether a family history of type 2 diabetes affected diabetes risk in CF patients in 539 families in the CF Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 38 publications
1
77
0
3
Order By: Relevance
“…46 The risk of CFRD may be increased if there is a family history of type 2 diabetes mellitus (T2DM), possibly because a gene linked to T2DM increases the risk and lowers the age of onset of CFRD. 47 …”
Section: Geneticsmentioning
confidence: 99%
“…46 The risk of CFRD may be increased if there is a family history of type 2 diabetes mellitus (T2DM), possibly because a gene linked to T2DM increases the risk and lowers the age of onset of CFRD. 47 …”
Section: Geneticsmentioning
confidence: 99%
“…Whereas the morphometric and biochemical risk factors for T2DM do not appear to be risk factors for CFRD, the genetics point to a relationship between T2DM and CFRD. For example, having a relative with T2DM increases the risk of a CF patient for developing CFRD (Blackman et al 2009a). In fact, the heritability of CFRD is high, approaching 1 (Table 1), substantially higher than for T2DM, suggesting that CFRD is much less influenced by environmental factors, such as diet, than T2DM with which it appears to share genetic etiology.…”
Section: Cf-related Diabetesmentioning
confidence: 99%
“…Twin studies suggest that the risk of CFRD closely correlates with certain genes associated with T2DM, such as TCF7L2. 55 Genome-wide association studies have identified four more novel genetic modifiers of CFRD: SLC26A9, CDKAL1, CDKN2A/B, and IGF2BP2, all of which are known susceptibility alleles for T2DM. 56 Given the variable development of CFRD in CF patients with DF508 and genes associated with T2DM, epigenetic factors may play a yet unknown role in the pathogenesis of CFRD.…”
Section: Pathophysiologymentioning
confidence: 99%